Consumers’ acceptance on Islamic home financing: empirical evidence on Bai Bithaman Ajil (BBA) in Malaysia - Abdul Razak, Dzuljastri; Mohamed, Mustafa Omar; Md Taib, Fauziah (2008)
Bai Bithaman Ajil (BBA) is the most predominant mode of home financing in Malaysia since the introduction of Islamic banking in 1983. BBA is a deferred installment sale where bank capitalizes its profit up front in the sale of property. The concept is similar to debt financing which is often resulted in high cost. BBA as practiced in Malaysia is seen not to be in compliant with the Shariah principle as the bank does not take the risk of ownership and liability on the property. Given the controversial features of BBA, it is anticipated that there is high level of dissatisfaction among the present and potential BBA customers including Muslim and the Non-Muslim. Based on a survey of 300 owners and potential house owners, there is high level of dissatisfaction among the customers as evidenced by their low intention to use BBA Muslim customers in general are concerned about the features of BBA notably its compliance with Shariah as well as its inability to fulfill the broad objective of justice, equality and societal well being. The Non-Muslim customers however seem to have greater beliefs in BBA and its ability to fulfill socially desirable objectives. The discontent feelings signal the urgent need by the bankers to come up with alternatives of Islamic home financing product. Musharakah Mutanaqisah or the Diminishing Partnership concept has been proposed to replace BBA for its esteemed features.